Coprocessing of a Turkish lignite with a cellulosic waste material - 2. The effect of coprocessing on liquefaction yields at different reaction pressures and sawdust/lignite ratios - Karaca, F; Bolat, E (ELSEVIER SCIENCE BV, 2002)
Most of the research works done for alternative energy sources have shown that, in general, coprocessing of coal with biomass-type wastes has a positive effect on the liquefaction yields and these materials are increasingly studied as coliquefaction agents for the conversion of coal to liquid fuels, Addition of biomass waste materials to coal is known to be synergetic in that it improves the yields and quality of liquid products produced from coal under relatively mild conditions of temperature and pressure, This paper reports the coprocessing of a Turkish lignite with sawdust in the category of biomass-type waste material. The experiments have been conducted in a stainless-steel reactor, and temperature and tetralin/(lignite+sawdust) ratio were kept constant at 350degreesC and 3:1 (vol/wt), respectively. This is the First time that the influence of reaction pressures on coliquefaction yields was investigated, In addition, the influence of the sawdust/lignite ratios on coprocessing conversion and product distribution was also investigated under the same reaction conditions. The runs were carried out at 10, 25, 40, 55, and 70 arm initial cold hydrogen pressure values and at 0,5: 1, 0.75:1, 1:1, 1.25:1, and 1.5:1 sawdust/lignite (wt/wt) ratio values. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: lignite; sawdust; liquefaction; coprocessing; COAL; COLIQUEFACTION; Chemistry; Energy & Fuels; Engineering